Preserving the chondrolabral junction reduces the rate of capsular adhesions. Issue 1 (19th March 2019) - Webb, Mark S L; Devitt, Brian M; O'Donnell, John M
Abstract: The operative treatment of pincer-type femoroacetabular impingement (FAI) has become an increasingly more common procedure. Classically, the labrum is incised at the chondrolabral junction (CLJ), or a concurrent tear is extended to allow access to the acetabular rim facilitating acetabuloplasty. The labrum is subsequently repaired using suture anchors. More recently, acetabuloplasty has been performed without incising the labrum and negating the need to use suture anchors. The aim of this study is to determine whether preserving the CLJ reduces the incidence of revision hip arthroscopy for the treatment of capsulolabral adhesions. This retrospective study compared two cohorts of patients undergoing hip arthroscopy for pincer-type FAI from August 2002 to April 2015. The groups analysed were patients undergoing acetabuloplasty with labral repair (LR) and those with no labral repair (NLR). The revision rates and causes for revision were compared using the χ 2 analysis. There were 1010 cases in total. Acetabuloplasty with LR was performed in 546 hips (519 patients), while acetabuloplasty with NLR was performed in 464 hips (431 patients). In the LR group, there were 54 (9.9%) revisions, 25 (46%) of which were due to capsulolabral adhesions. The NLR group had 36 (7.8%) revisions with six (17%) due to capsulolabral adhesions. Preserving the CLJ, thereby avoiding the need for drilling and the insertion of suture anchors, when performing an acetabuloplasty for pincer-type FAI, significantly reduces the rate of symptomatic adhesions requiring revision arthroscopy.